KEARIFAN LOKAL MASYARAKAT MUNA DALAM PENGELOLAAN HASIL PANEN JAGUNG SEBAGAI UPAYA MENJAGA KETAHANAN PANGAN - Marhini, La Ode; Harjoprawiro, La; Malik, Elmy Selfiana; Saputri, Shinta Arjunita; Rihu, Agus (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
Limited resources require people to be wise and creative to exist in the particular demographic circumtances. This is also perceived by the people in Liangkabhori village, Muna Regency. The condition of the karst hilly soil and the limited supply of water as well as seasonal changes that are sometimes uncertain require the community to maximize harvest and effective storage so that food supplies are always available. This study aims to describe the vocabulary of corn hasrvest and local wisdom of the Muna community in Liangkabhori village in managing corn harvests as an effort to maintain food sustainability. The research method uses a qualitative descriptive approach. The results show that in an effort to maintain food security, the community has local knowledge in the process of managing corn harvests so that the harvest can still be consumed in the long term. The series of harvest management processes are (1) knowledge of the estimated harvest period of corn which is determined by three things, namely the age of corn, the appearance or visuality of corn fruit or corn leaves and weather conditions at harvest. (2) knowledge of the harvesting process (detongka) and initial treatment of newly harvested corn, (3) knowledge of sorting corn (Depinde), namely corn is selected and sorted and categorized into five types, namely perapi corn, kampuru corn, obunta corn, kamansighonu-ghonu corn and obhoka corn, (4) cleaning of corn cobs and hairs (Detoto) and (5) Storage (Kasoria)